Caregiving burden, social support, and psychological well-being among family caregivers of older Italians: a cross-sectional study - Ramona Bongelli; Gianluca Busilacchi; Antonio Pacifico; Michele Fabiani; Carmela Guarascio; Federico Sofritti; Giovanni Lamura; Sara Santini (Frontiers Media S.A., 2024)
ObjectivesThis study aimed to identify factors affecting the psychological well-being of family caregivers of dependent older adults in Italy. Understanding these variables is essential for designing interventions to prevent negative outcomes in at-risk caregivers. The research explored how varying levels of caregiving burden and types of perceived social support influence psychological well-being.MethodsA cross-sectional study was conducted among 387 family caregivers of older adults in the Marche region (Italy) between November 2019 and March 2020. Data were collected via a structured questionnaire assessing psychological well-being (WHO-5 Well-Being Index), caregiving burden, and social support (COPE Index). Statistical analyses were performed using Jamovi software, with a significance threshold set at p < 0.05.ResultsA significant negative correlation was found between caregiving burden and psychological well-being [r (364) = − 0.540, p < 0.001], with caregiving burden being a significant predictor of psychological well-being reduction (R2 = 0.290; F = 150, p < 0.001). A threshold value of 2 (on a 1-4 scale) was identified, where caregiving burden predicted a significant reduction in psychological well-being. Conversely, greater perceived social support was positively correlated with better psychological well-being [r (357) = 0.348, p < 0.001] and was a significant predictor of it [R2 = 0.121; F = 49.2, p < 0.001]. Support from social and health services had the most notable impact on psychological well-being. Moreover, social support mitigated the negative impact of caregiving burden on psychological well-being.ConclusionThe study confirms that high caregiving burden adversely affects caregivers' psychological well-being, while social support plays a protective role. These findings highlight the need for interventions focused on reducing caregiving burden and enhancing support systems for family caregivers.